1998
DOI: 10.1111/j.1600-0897.1998.tb00345.x
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial Leukemia Inhibitory Factor (LIF) as a Possible Cause of Unexplained Infertility and Multiple Failures of Implantation

Abstract: In the majority of infertile women there is a deregulation of LIF production in the endometrium during both the proliferative and the secretory phases of the cycle. The dysfunction of cytokine production is more profound in patients with MFI. The deregulation of endometrial LIF secretion throughout the menstrual cycle may be a possible cause of unexplained infertility and repetitive failures of implantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
110
0
8

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 204 publications
(122 citation statements)
references
References 31 publications
4
110
0
8
Order By: Relevance
“…Recent studies further demonstrate that uterine conditional deletion of Stat3 also induces implantation failure (Lee et al, 2013, Pawar et al, 2013, Sun et al, 2013. In the human, a low level of LIF is associated with unexplained recurrent abortion and infertility (Hambartsoumian, 1998, Piccinni et al, 1998. These findings collectively indicate that the LIF-LIRFR/gp130-Stat3 axis is essential for normal embryo implantation.…”
Section: Cytokinesmentioning
confidence: 63%
“…Recent studies further demonstrate that uterine conditional deletion of Stat3 also induces implantation failure (Lee et al, 2013, Pawar et al, 2013, Sun et al, 2013. In the human, a low level of LIF is associated with unexplained recurrent abortion and infertility (Hambartsoumian, 1998, Piccinni et al, 1998. These findings collectively indicate that the LIF-LIRFR/gp130-Stat3 axis is essential for normal embryo implantation.…”
Section: Cytokinesmentioning
confidence: 63%
“…45 The presence of a sufficient amount of human LIF protein in the uterus at the time of implantation has been suggested as an essential condition for implantation. 46 It is possible that p53 plays a similar role in human fecundity through regulation of uterine LIF levels at the implantation stage. Indeed, a study from Carolyn Coulum's group reported that the P72 allele of the p53 gene, which has an altered p53 transcriptional activity compared to the R72, is associated with the recurrent implantation failure in an IVF clinic.…”
mentioning
confidence: 99%
“…DOI: 10.3109/19396368.2013.862316 A reduced endometrial receptivity has been correlated with an increasing number of women with unexplained infertility [Strowitzki et al 2006]. Previous studies have shown diminished expression of integrin [Lessey et al 1995], selectin [Foulk et al 2007], and LIF [Laird et al 1997;Hambartsoumian 1998] amongst unexplained infertile women. In a previous study, it is documented that endometrial LIF levels following ovulation induction with CC were comparable to spontaneous cycles in women with unexplained infertility [Kuscu et al 2002].…”
Section: Discussionmentioning
confidence: 99%